Strategic human resource management - Nankervis, Alan R.; Compton, Robert L.; McCarthy, Terence E. (South Melbourne : Nelson, 1999)
This book is about: Perspectives of strategic human resource management; Human resource planning; Staffing the restructured workplace; Ensuring the effectiveness of human resource management; ...
Keywords: Management; Industrial relations; Personnel management -- Australia; Personnel management; Industrial relations; Industrial relations -- Australia